IMPLEMENTASI KURIKULUM BERBASIS INDUSTRI DI SMK MITRA INDUSTRI MM2100 CIKARANG - BEKASI - Bambang Nurcahyono; Rita Retnowati; Entis Sutisna (JURNAL MANAJEMEN PENDIDIKAN, 2020)
INDUSTRIAL BASED CURRICULUM IMPLEMETATION AT SMK MITRA INDUSTRI MM2100 CIKARANG-BEKASIThis study aims to obtain a fact-based picture in the form of data and information regarding the implementation of an industry-based curriculum at SMK Mitra Industri MM2100. This study uses a qualitative method, which is to make a complex and comprehensive picture with detailed descriptions from the eyes of the informants to produce a comprehensive exposure based on clear and real findings, events, processes and results related to the implementation of an industry-based curriculum. Data obtained through interviews, field observations and documentation studies. Based on data analysis, the following results are obtained: 1). The curriculum development model used at SMK Mitra Industri MM2100, is a model of curriculum development that is problem-centered by integrating several disciplines to form a concept of attitudes, skills and knowledge in accordance with the demands and needs of the industry which are oriented to the vision, mission and goals of the school. 2). The learning process at SMK Mitra Industri MM2100 uses a block system, which is designed to be oriented towards the merging of instruction and construction, so that the learning process approach refers to the dual base program to fully and fully cultivate industrial work patterns. 3). Challenges and obstacles in the implementation of industrial-based curriculum in SMK Mitra Industri MM2100 in the form of not wanting to change the principles of school/mental blockage, focusing on knowledge, school target is focus on graduation of students, not on the distribution of work at industries and bad networking with industry which can be overcome through socialization to all elements of the school and stakeholders involved.